2010
DOI: 10.14429/dsj.60.360
|View full text |Cite
|
Sign up to set email alerts
|

Adhesively-bonded Patch Repair with Composites

Abstract: Adhesively-bonded composite patch repairs over cracked or corrosion-damaged metallic aircraft structures have shown great promise for extending life of ageing structures. This study presents the numerical investigation into the interface behaviour of adhesively-bonded cracked aluminum alloy substrate patched with fibre-reinforced composite material. The adhesive is modelled as an elasto-plastic bilinear material to characterise the debond behaviour, while the defective substrate is regarded as linear elastic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The determining other issues are that choosing the suitable patch for the damaged materials, measuring the strength of the damaged materials after applying the patch. The 49 researches about composite materials increase and they are used by basis and auxiliary material in the most of the recent applications (Çalışkan et al, 2017, Maamar et al, 2015, Pandey and Kumar, 2010, Kwon and Hall, 2015, Coelho et al, 2017, Deng et al, 2017. Impact response of material may depend on its application area and aim.…”
Section: Introductionmentioning
confidence: 99%
“…The determining other issues are that choosing the suitable patch for the damaged materials, measuring the strength of the damaged materials after applying the patch. The 49 researches about composite materials increase and they are used by basis and auxiliary material in the most of the recent applications (Çalışkan et al, 2017, Maamar et al, 2015, Pandey and Kumar, 2010, Kwon and Hall, 2015, Coelho et al, 2017, Deng et al, 2017. Impact response of material may depend on its application area and aim.…”
Section: Introductionmentioning
confidence: 99%
“…Pandey and Kumar 12 showed that composite patch repairs of cracked metallic aircraft structures extend their life. They presented the numerical calculation into the interface behavior of repaired aluminum alloy plates patched by fiber composites.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesively-bonded composite patch repair over cracked or corrosion-damaged metallic aircraft structures has shown great promise for extending life of aging structures [1][2][3][4][5][6]. Due to the existence of the bonded patches, the stress concentration of the damaged areas is greatly improved [7][8][9].…”
Section: Introductionmentioning
confidence: 99%